PENGGUNAAN MULTIMEDIA INTERAKTIF FUN WORD BERBASIS COMPUTER ASSISTED INSTRUCTION (CAI) UNTUK MENINGKATKAN PENGUASAAN KOSAKATA ANAK AUTIS - Mezalina, Lina (Jurnal Pendidikan Khusus, 2017)
ABSTRACT: Problems in the field of communication autistic children one of them is the level of vocabulary mastery is low. The purpose of this study is to prove the use of interactive multimedia Fun Word based Computer Assisted Instruction (CAI) to improve the mastery of the vocabulary of children with autism. The developed vocabulary is the vocabulary used in everyday life. This research uses quantitative research approach with pre-experimental research type, and one-group pretest-posttest design. Subjects in this study were 6 children of class III autism in SDLB Krida Utama. Technique of collecting data that is in the form of test. While the technique of data analysis using non parametik statistic with Wilcoxon test. The results showed that before the treatment / pre-test the average value obtained was 52.1 and after the treated / post-test the average value obtained for 64.1. Value Zh = 2.20 is greater than the crisis value of 5% Zt = +1,96 which means Ho is rejected and Ha accepted, so it can be concluded that the use of interactive multimedia Fun Word based Computer Assisted Instruction (CAI) significantly influence the mastery of vocabulary children with autism.     Keywords: Interactive Multimedia, Computer Assisted Instruction (CAI), Vocabulary